Organophosphorus S-adenosyl-L-methionine mimetics: synthesis, stability, and substrate properties - Rudenko, Alexander Yu; Mariasina, Sofia S.; Bolikhova, Anastasiia K.; Nikulin, Maxim V.; Ozhiganov, Ratislav M.; Vasil’ev, Vasiliy G.; Ikhalaynen, Yuri A.; Khandazhinskaya, Anastasia L.; Khomutov, Maxim A.; Sergiev, Peter V.; Khomutov, Alex R.; Polshakov, Vladimir I. (Frontiers in Chemistry, 2024)
S-Adenosyl-L-methionine (SAM)-mediated methylation of biomolecules controls their function and regulates numerous vital intracellular processes. Analogues of SAM with a reporter group in place of the S-methyl group are widely used to study these processes. However, many of these analogues are chemical unstable that largely limits their practical application. We have developed a new compound, SAM‑PH, which contains an H phosphinic group ( P(O)(H)OH) instead of SAM carboxylic group. SAM‑PH is significantly more stable than SAM; retains functional activity in methyltransferase WBSCR27, associated with Williams-Beuren syndrome WBSCR27, and сatechol O methyltransferase reactions. Rac-SAM‑PH was synthesized chemically, while (R,S) SAM‑PH and its analogues were prepared enzymatically either from H‑phosphinic analogues of methionine (Met-PH), or H‑phosphinic analogue of S adenosyl L homocysteine (SAH‑PH), using methionine adenosyltransferase 2A or halide methyltransferases, respectively. SAH‑PH undergo glycoside bond cleavage in the presence of methylthioadenosine nucleosidase like natural SAH. Thus SAM‑PH and its analogues are a promising new tool for investigating methyltransferases and incorporating reporter groups into their substrates.